Peran Pengendalian Internal dan Whistleblowing System dalam Pencegahan Fraud (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the role of internal control and whistleblowing system in fraud prevention through a literature review appoarch. The background of this study is based on the persistenly high incidence of fraud cases that arise due to the suboptimal monitoring system and minimal compliance with applicable regulations in the organizations. Technique used is a literature review by examining varios relevant previous studies published between 2021-2025, obtained from google scholar. The result of the review indicate a significant correlation between internal control and whisteblowing system in efforts to prevent fraud in organizations in Indonesia. Internal control has a positive effect on fraud prevention efforts. Meanwhile, the whistleblowing system serves as a secure reporting mechanism, although several previuos studies show inconsistent result regarding its influence. The implication of this study highlights the importance of implementing effective internal control supported by an optimal whistleblowing system to enhance fraud prevention efforts within an organization.